"Clicking" Polymers or Just Efficient Linking: What Is the Difference? - Barner-Kowollik, Christopher; Du Prez, Filip E.; Espeel, Pieter; Hawker, Craig J.; Junkers, Thomas; Schlaad, Helmut; Van Camp, Wim (Angewandte Chemie International Edition, 2011)
The “click” trick: Many reactions are classified as click reactions even though some are limited to certain applications. Thus, there is danger that the term “click” will become meaningless over time and simply a synonym for “successful”. To prevent this, the original click criteria are evaluated in this Essay specifically for the synthetic polymer field and a set of criteria are specified that distinguishes click from other efficient reactions.